2018
DOI: 10.3390/ijms19071832
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Acetate Extract of Scindapsus cf. hederaceus Exerts the Inhibitory Bioactivity on Human Non-Small Cell Lung Cancer Cells through Modulating ER Stress

Abstract: Unfolded protein response (UPR) is a cytoprotective mechanism that alleviates the protein-folding burden in eukaryotic organisms. Moderate activation of UPR is required for maintaining endoplasmic reticulum (ER) homeostasis and profoundly contributes to tumorigenesis. Defects in UPR signaling are implicated in the attenuation of various malignant phenotypes including cell proliferation, migration, and invasion, as well as angiogenesis. This suggests UPR as a promising target in cancer therapy. The pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…About this, it has recently been shown that an ethyl acetate extract from Scindapsus cf. hederaceus (SH-EAE), by decreasing the expression of PERK and IRE1α, exerts anti-proliferative and anti-migratory activities in human lung cancer cells; moreover experiments in zebrafish demonstrated that a decreased expression of PERK and IRE1α in SH-EAE-treated lung cancer cells is accompanied by the reduction of vessels development, suggesting an antiangiogenic effect [ 131 ]. The expression of ER stress sensor BiP may be enhanced in metastatic cells, and BiP could represent an advantageous therapeutic target [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…About this, it has recently been shown that an ethyl acetate extract from Scindapsus cf. hederaceus (SH-EAE), by decreasing the expression of PERK and IRE1α, exerts anti-proliferative and anti-migratory activities in human lung cancer cells; moreover experiments in zebrafish demonstrated that a decreased expression of PERK and IRE1α in SH-EAE-treated lung cancer cells is accompanied by the reduction of vessels development, suggesting an antiangiogenic effect [ 131 ]. The expression of ER stress sensor BiP may be enhanced in metastatic cells, and BiP could represent an advantageous therapeutic target [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…ER stress is found to be a new pathway leading to apoptosis [52]. In recent studies, ER stress is considered to be associated with angiogenesis [53,54], but the mechanism is not well understood. In our previous studies, drug-induced ER stress inhibits the activation of p-STAT3 [1,12].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation www.nature.com/scientificreports/ for the low and high peptide concentrations required for significant growth inhibition of various cancer cells described above is owing to several factors including the possibility of DKPs binding to serum proteins in the culture medium, and drug efflux by P-glycoprotein, or the lack of sufficient absorption of peptides into the cells 25 . A key mechanism involved in the action of many anticancer drugs is the activation of extrinsic and intrinsic apoptotic pathways [31][32][33][34] . The crucial element in the intrinsic apoptotic pathway is the efflux of Cytc from mitochondria to the cytosol.…”
Section: Discussionmentioning
confidence: 99%